Coronavirus Disease 2019 (COVID-19) Vaccination Coverage, Intentions, Attitudes, and Barriers by Race/Ethnicity, Language of Interview, and Nativity—National Immunization Survey Adult COVID Module, 22 April 2021–29 January 2022 . (23rd June 2022) - Ohlsen, Elizabeth C; Yankey, David; Pezzi, Clelia; Kriss, Jennifer L; Lu, Peng Jun; Hung, Mei Chuan; Bernabe, Maria I Dionicio; Kumar, Gayathri S; Jentes, Emily; Elam-Evans, Laurie D; Jackson, Hannah; Black, Carla L; et al.
Abstract: The National Immunization Survey Adult COVID Module used a random-digit-dialed phone survey during 22 April 2021–29 January 2022 to quantify coronavirus disease 2019 (COVID-19) vaccination, intent, attitudes, and barriers by detailed race/ethnicity, interview language, and nativity. Foreign-born respondents overall and within racial/ethnic categories had higher vaccination coverage (80.9%), higher intent to be vaccinated (4.2%), and lower hesitancy toward COVID-19 vaccination (6.0%) than US-born respondents (72.6%, 2.9%, and 15.8%, respectively). Vaccination coverage was significantly lower for certain subcategories of national origin or heritage (eg, Jamaican [68.6%], Haitian [60.7%], Somali [49.0%] in weighted estimates). Respondents interviewed in Spanish had lower vaccination coverage than interviewees in English but higher intent to be vaccinated and lower reluctance. Collection and analysis of nativity, detailed race/ethnicity and language information allow identification of disparities among racial/ethnic subgroups. Vaccination programs could use such information to implement culturally and linguistically appropriate focused interventions among communities with lower vaccination coverage. Abstract : Foreign-born survey respondents reported higher COVID-19 vaccination uptake than US-born respondents. Certain subcategories and Spanish language interviewees reported lower uptake. Collection and analysis of nativity, detailed race/ethnicity, and language information allow identification of disparities and can help inform focused interventions.